Representation of Moral Values in the Legend of the Tadulako Statue - Dita Indah Sari Monai; Nelvin Lage; Syamsuddin; Nirmayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The Legend of the Tadulako Statue was chosen as the object of this research because it is one of the oral traditions of the Behoa tribe that still survives to this day, especially in the form of stone monuments, so the moral narrative behind it is at risk of being forgotten even though the site is still widely known. This study aims to describe the representation of moral values in the Legend of the Tadulako Statue from Poso Regency, Central Sulawesi Province, using descriptive qualitative methods with thematic analysis. Data were collected through in-depth interviews with four key informants in Doda Village and analyzed using the Miles and Huberman interactive model. The analysis of moral values uses the framework of Kees Bertens (2018), which classifies moral values into four categories—relationships with God, oneself, fellow human beings, and nature—combined with Stuart Hall's (1997) theory of representation; Bertens explains what moral values are present, while Hall explains how these values are constructed and circulated through meaning-making practices. The novelty of this research lies in the study of the Behoa legend, which has never been documented academically, analyzed through Bertens' four categories of moral values and Hall's representational lens. The results of the study show that this legend is rich in moral values represented through characters and events: individual and social values appear most dominant, while religious and natural values appear more briefly but play an important role at the beginning and climax of the story. This research contributes to the study of regional folklore that is still minimally documented and the development of character education based on local wisdom, while also emphasizing the urgency of documenting regional oral traditions that are threatened with extinction before they eventually only leave physical monuments without accompanying moral meaning.